2001
DOI: 10.1039/b105272c
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Zirconium oxide thin films have been deposited by atomic layer epitaxy (ALE) using Zr(thd) 4 , Cp 2 Zr(CH 3 ) 2 and Cp 2 ZrCl 2 (thd~3,3,5,5-tetramethylheptane-3,5-dionate, Cp~cyclopentadienyl) as zirconium precursors and ozone as the oxygen source. A plateau of constant growth rate (ALE window) was observed for the Zr(thd) 4 / O 3 process at 375-400 uC, for Cp 2 Zr(CH 3 ) 2 /O 3 at 310-365 uC and for Cp 2 ZrCl 2 /O 3 at 275-350 uC. Within these temperature ranges constant deposition rates of 0.24, 0.55 and 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 60 publications
(77 reference statements)
1
71
1
Order By: Relevance
“…It is also worth noting that the growth rates for each of the oxides are similar to what is reported in some literature studies on nonporous substrates. 18,19 LaFeO 3 films were grown by sequential deposition of La 2 O 3 and Fe 2 O 3 , alternating between three cycles of La 2 O 3 and one of Fe 2 O 3 ALD cycle to ensure proper mixing of the stoichiometric amounts of each oxide. The 3:1 cycle ratio was calculated to give a 1:1 molar ratio of La and Fe based on the growth rates in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…It is also worth noting that the growth rates for each of the oxides are similar to what is reported in some literature studies on nonporous substrates. 18,19 LaFeO 3 films were grown by sequential deposition of La 2 O 3 and Fe 2 O 3 , alternating between three cycles of La 2 O 3 and one of Fe 2 O 3 ALD cycle to ensure proper mixing of the stoichiometric amounts of each oxide. The 3:1 cycle ratio was calculated to give a 1:1 molar ratio of La and Fe based on the growth rates in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Volatile and reactive cyclopentadienyl (Cp, -C 5 H 5 ) complexes are known to react with water, and furthermore the growth rates obtained in Cp-based processes have been markedly high. [38] Cyclopentadienyl complexes have previously been used by us in the ALD of some rare earth oxides, namely Sc 2 O 3 [30] and Y 2 O 3 . [39] Additionally, Lu 2 O 3 thin films have been grown by ALD using a dimeric Lu precursor containing silylated Cp groups.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of precursors such as ZrCl 4 , 14-17 ZrI 4 , 18,19 Zr (OBu) 4 , 20 Zr(thd) 4 , 21 Zr(OBu)(dmae) 2 22 have been used in the past but suitability of the alkoxide limits application of the precursors. Zirconium oxychloride octahydrate (ZrOCl 2 ․ 8H 2 O) has been also used in fabrication of thin film of zirconium oxide (ZrO2) using a sol-gel method but the method needs extra care, greater process time and high cost.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 It has been reported 25 that β-diketonates and their derivatives are more stable and readily soluble in organic solvent than alkoxides and can be used successfully for ceramic thin film deposition. [26][27][28][29] Keeping all these difficulties in view, we adopted a sonochemical method for the synthesis of precursor [Zr(acac) 3 30 In the past years sonochemical synthetic technique has largely been applied to organic synthesis and little attention was paid to synthesize inorganic materials for commercial utility. It is also observed that metal halides and metal acetylacetonate react with alkali metals sonochemically and give reactive metal (M + ) that reacts instantly with organic ligands to yield respective metal organic complexes.…”
Section: Introductionmentioning
confidence: 99%